Pakistan at the precipice: The looming threat of measles amidst the COVID-19 pandemic - Samiuddin Tariq; Faizan Niaz; Yusra Afzal; Rabbia Tariq; Abdulqadir J. Nashwan; Irfan Ullah; Irfan Ullah (Frontiers Media S.A., 2022)
The global focus on curbing the COVID-19 pandemic has reduced the overall immunization rates worldwide. This, coupled with increasing malnutrition and strained healthcare, has increased measles cases and mortality globally. Many countries are thus facing outbreaks, with Afghanistan having reported 372 deaths between January and September 2022. Therefore, Pakistan, a country in a similar economic state and the world's fourth highest reported measles cases in 2022, must take action. Moreover, the current flooded state of Pakistan and the subsequent mass movement of population, deterioration of health services, and worsened living conditions all contribute to put the country at a high risk of potentially devastating Measles outbreaks. With vaccination rates down by 42% since the start of the pandemic and the threat of an outbreak increasing daily, there is only so much time before the situation spirals out of control.